2021
DOI: 10.1002/biof.1770
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining the serum 25‐hydroxyvitamin D response to vitamin D supplementation: Data mining approach

Abstract: Vitamin D supplementation has been shown to prevent vitamin D deficiency, but various factors can affect the response to supplementation. Data mining is a statistical method for pulling out information from large databases. We aimed to evaluate the factors influencing serum 25-hydroxyvitamin D levels in response to supplementation of vitamin D using a random forest (RF) model. Data were extracted from the survey of ultraviolet intake by nutritional approach study. Vitamin D levels were measured at baseline and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In equation ( 4), _ PM PLAntennaGain represents the antenna gain in the distance from the base station to the grid point, and OtherLoss represents other losses in the distance. Based on this, the information expression of grid fingerprints can also be obtained as equation (5). In equation ( 5), BSPWR for the transmission power of the target area, subtracting the transmission power from the total path loss can obtain the field strength information in the grid points, which is the grid fingerprint information.…”
Section: Research On the Demand Determination Methods And Precision M...mentioning
confidence: 99%
See 1 more Smart Citation
“…In equation ( 4), _ PM PLAntennaGain represents the antenna gain in the distance from the base station to the grid point, and OtherLoss represents other losses in the distance. Based on this, the information expression of grid fingerprints can also be obtained as equation (5). In equation ( 5), BSPWR for the transmission power of the target area, subtracting the transmission power from the total path loss can obtain the field strength information in the grid points, which is the grid fingerprint information.…”
Section: Research On the Demand Determination Methods And Precision M...mentioning
confidence: 99%
“…This study evaluated 76 factors including body mass index and total bilirubin, and validated the correlation. Finally, the evaluation accuracy of random forest model is 93% [5]. In order to solve the environmental pollution problem in blast furnace ironmaking, Kou et al established six evaluation systems, processed them using Python, identified potential factors, and then established a comprehensive evaluation model through factor analysis.…”
Section: Related Workmentioning
confidence: 99%
“…They achieved an accuracy rate of 93% using RF to determine the factors affecting the response of vitamin D supplementation. 30 Padmajaa et al (2021) used machine learning algorithms including RF, multi-layer perceptron, k-nearest neighbor, SVM, decision tree, gradient boosting, stochastic gradient descent, adaboost classifier, extra trees classifier algorithm, and LR. In their study in which the prognosis of vitamin D deficiency severity was estimated and extra trees classifier algorithm achieved an accuracy rate of 73.3%.…”
Section: Related Studiesmentioning
confidence: 99%